The Relationship between Occupational Stress and Work Ability among Midwives in Mashhad, Iran - Masoumeh Kordi; Soheila Mohamadirizi; Mohamad Taghi Shakeri; Morteza Modares Gharavi; Javad Salehi Fadardi (Mashhad University of Medical Sciences, 2014)
Background and Aim: Occupational stress is one of the key factors in reducing staff productivity in organizations with physical and psychological impacts on employees. Nursing and midwifery are among the most stressful professions. Therefore, this study aimed to determine the relationship between occupational stress and work ability of midwives in Mashhad, Iran in 2011. Materials and Methods: This cross-sectional study was carried on 123 midwives employed in the public hospitals and health centres in Mashhad, Iran using two-stage sampling method. Demographic and work-related data were obtained through a self-structured questionnaire. Occupational stress and work ability were measured using Occupational Stress Assessment Questionnaire (OSAQ) and Work Ability Index Questionnaire (WAIQ). The statistical analysis was performed using student's t-test, One Way ANOVA, correlation coefficient, and linear regression model through SPSS statistical software (version 11.5).   Results: The results showed that the mean score of occupational stress and work ability was 149 ± 0.01 and 38.81±0.05, respectively. There was a negative correlation between job-related stress and work ability. Midwives with higher occupational stress experienced poorer work ability (P=0.021, r=-0.061).   Conclusion: Sever work stress is associated with reduced work ability. So it is recommended to eliminate or decrease occupational stress and increase work ability among Iranian midwives using preventive measures, although identification of sources of occupational stress seems necessary in order to adopt appropriate stress management strategies.